Agricultural commercialization and sustainable land management practices in Ghana - Martey, E.; Etwire, P.M.; Abdoulaye, T. (2025)
Agricultural commercialisation is a strategy for transiting farmers from subsistence to market-oriented agriculture for rural economic growth. Several studies have linked agricultural commercialization to productivity, poverty, expenditure, and food security with little attention to sustainable land management (SLM). Using panel household survey data of maize producers, we evaluate the effects of maize commercialisation on SLM. We controlled for time-invariant unobserved heterogeneity using a household fixed-effect estimator and accounted for possible endogeneity using an instrumental variable approach. To check for the robustness of the results, we further employed the Lewbel 2SLS and conducted heterogeneity analysis based on gender, age, food security status, and farm size. We observed a positive effect of maize commercialisation on the area under tree cultivation and the intensity of SLM practices adopted. A transmission channel analysis indicates that income is a potential channel through which maize commercialisation influences SLM and the area under tree cultivation. Therefore, policy that enhances agricultural commercialisation is essential for strengthening sustainable land use while protecting land resources and the ecosystem functions.